PENDAMPINGAN STRATEGI PEMASARAN DIGITAL BAGI PELAKU USAHA KULINER LOKAL DI DESA JIMBARAN KABUPATEN BADUNG - Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Sujana; I Made Wisnu Wardana (Nusantara Hasana Journal, 2022)
The rapid development of information technology has transformed traditional marketing approaches into digital-based marketing systems. Local culinary entrepreneurs are required to utilize digital technologies to improve competitiveness and expand market reach. Jimbaran Village, as one of the leading tourism destinations in Badung Regency, is home to numerous local culinary businesses that contribute significantly to the tourism sector. However, many entrepreneurs still face challenges in implementing digital marketing strategies, including limited digital literacy, inadequate promotional content creation skills, and underutilization of social media platforms. This community service program aimed to enhance the competencies of local culinary entrepreneurs through digital marketing strategy assistance. The methods employed included socialization, digital marketing training, promotional content creation workshops, social media mentoring, and program evaluation. A total of 40 local culinary entrepreneurs participated in the program. The results demonstrated significant improvements in participants’ understanding of digital marketing, business branding, social media management, and digital promotion strategies. Furthermore, participants successfully implemented digital marketing practices to increase business visibility and reach broader consumer segments. This program contributed positively to strengthening the competitiveness of local culinary businesses in the Jimbaran tourism area.